Pemetaan Riset Akuntansi Zakat (PSAK 109) Berbasis Analisis Blibiometrik Dan Vosviewer - Anisah Hanan Nabilah; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to map and analyze the development of zakat accounting research and identify the latest trends developing in this field. This research uses bibliometric approach to achieve the objective, which is by analyzing research publications related to zakat accounting. This approach allows researchers to understand the development of knowledge in the field of zakat accounting and identify future research opportunities. The data source of this research is metadata collected using Google Scholar, covering publications from 2019 to 2024. The metadata was then exported into RIS format and analyzed using VOSviewer software. This study found that the newest topic in zakat accounting research is